Carrying Capacity and Population Food Balance of District Bulandshahr, Uttar Pradesh - Khan, Mohammad Shah Nawaz; Khan, Mohd. Mazhar Ali (National Geographical Journal of India, 2022)
The study of carrying capacity of land and population food balance in district Bulandshahr is an attempt to understand the man and land relationship. It helps in finding out the relative population pressure on the available arable land in different blocks of the district. In the contemporary world, where the problems of food crisis and over population are real; an analysis of the carrying capacity of land is of great importance. The increasing pressure of population on the available resources is a matter of great concern to the present day academicians, planners and policy makers. Geographers are spatially concerned with deteriorating man and land relationship (Gharge, 2011). The idea of carrying capacity relates closely to that of sustainable development, because both refer to the need of survival rather than capital. However, in future it is recommended to bring down the population pressure so as to avoid any decline in the carrying capacity of the land. There is a close relationship between numbers of heads of persons and the carrying capacity of the land, particularly in an agrarian society where land is almost the sole support of the growing population. The supply of agricultural land is almost fixed in aerial extent while population is increasing rapidly. Estimation of carrying capacity using food production is carried out by dividing total food production by the standard level of food consumption of the area. The result is a population that can be supported at a given level of subsistence assuming that food is equitably distributed. In simplest words carrying capacity of land is about food production and population